Dismantling the welfare state?: after twenty-five years : what have we learned and what should we learn? - Jensen, Carsten; Wenzelburger, Georg; Zohlnhöfer, Reimut (Journal of European social policy, 2019)
Dismantling the Welfare State? is a modern classic in the welfare state literature. Yet although the book is widely known, the ‘Piersonian argument’ as it is ty...
Gesehen am 15.01.2020